2021
DOI: 10.18823/asiatefl.2021.18.4.14.1302
|View full text |Cite
|
Sign up to set email alerts
|

Learner Perceptions of Demotivators in the EFL Classroom : Conceptual Framework and Scale Development

Abstract: Grounded in social cognitive theory and expectancy-value theory, the current study aimed to present a demotivation scale -Learner Perceptions of Demotivators Scale (LPDS)designed specifically for use in L2 research and tested empirically to provide evidence of its construct, validity, and reliability. Study 1 sample consisted of 295 Chinese college English learners. An exploratory factor analysis offered preliminary support for a factor structure comprising three dimensions: negative teacher behavior, loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…In other words, these four factors are perceived as strong demotivating factors by Chinese EFL college students in blended learning environment. This finding lend support to many previous studies which showed factors related to learning environment (Gorham and Christophel, 1992;Christophel and Gorham, 1995;Gorham and Millette, 1997;Zhang, 2007;Sakai and Kikuchi, 2009;Kikuchi, 2011;Krishnan and Pathan, 2013;Xie et al, 2018;Adara et al, 2021;Xie et al, 2021;Huwari et al, 2023), teachers (Gorham and Christophel, 1992;Christophel and Gorham, 1995;Gorham and Millette, 1997;Zhang, 2007;Katt and Condly, 2009;Kikuchi and Sakai, 2009;Krishnan and Pathan, 2013;Xie et al, 2018;Adara et al, 2021;Xie et al, 2021;Huwari et al, 2023), intrinsic motivation (Gorham and Christophel, 1992;Christophel and Gorham, 1995;Gorham and Millette, 1997;Zhang, 2007;Sakai and Kikuchi, 2009;Kikuchi, 2011;Krishnan and Pathan, 2013;Çankaya, 2018;Xie et al, 2018Xie et al, , 2021 are strong demotivating factors. However, the mean score of Loss of Task Value factor is the lowest (1.87).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In other words, these four factors are perceived as strong demotivating factors by Chinese EFL college students in blended learning environment. This finding lend support to many previous studies which showed factors related to learning environment (Gorham and Christophel, 1992;Christophel and Gorham, 1995;Gorham and Millette, 1997;Zhang, 2007;Sakai and Kikuchi, 2009;Kikuchi, 2011;Krishnan and Pathan, 2013;Xie et al, 2018;Adara et al, 2021;Xie et al, 2021;Huwari et al, 2023), teachers (Gorham and Christophel, 1992;Christophel and Gorham, 1995;Gorham and Millette, 1997;Zhang, 2007;Katt and Condly, 2009;Kikuchi and Sakai, 2009;Krishnan and Pathan, 2013;Xie et al, 2018;Adara et al, 2021;Xie et al, 2021;Huwari et al, 2023), intrinsic motivation (Gorham and Christophel, 1992;Christophel and Gorham, 1995;Gorham and Millette, 1997;Zhang, 2007;Sakai and Kikuchi, 2009;Kikuchi, 2011;Krishnan and Pathan, 2013;Çankaya, 2018;Xie et al, 2018Xie et al, , 2021 are strong demotivating factors. However, the mean score of Loss of Task Value factor is the lowest (1.87).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, although this factor (factor 2) was extracted as a demotivating factor, the majority of the participants (82.2%) did not consider it to be demotivating. This factor was borrowed from Xie's research (Xie et al, 2018(Xie et al, , 2021, however, results from this paper show that most participants did not consider it as demotivating. In other words, most participants believe English and learning English are of great value, which could be supported by the fact that more than 1.35 billion people around the world speak English and about 360 million people speak English as their first language, and English is the most commonly spoken and studied foreign language in the world (Lyons, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The purpose of the current study was to trace demotivation back to its origin by examining demotivator attribution differences between regular non-English major students and students who are enrolled in a dual degree English program. This study utilized the Learner Perceptions of Demotivators Scale (Xie et al, 2021) to gauge three demotivating factors including negative teacher behavior, loss of task value, and low expectancy for success. Data were collected from a sample of 320 undergraduate students in China.…”
mentioning
confidence: 99%